Macrocyclic copper(II) complexes - Fernandes, Ana S. (2015)
Synthetic superoxide dismutase mimetics have emerged as a potential novel class of drugs for the treatment of oxidative stress related diseases. Among these agents, metal complexes with macrocyclic ligands constitute an important group. In this work we synthesized five macrocyclic copper(II) complexes and evaluated their ability to scavenge the superoxide anions generated by the xanthine-xanthine oxidase system. Two different endpoints were used, the nitro blue tetrazolium (NBT) reduction assay (colorimetric method) and the dihydroethidium (DHE) oxidation assay (fluorimetric method). IC50 values in the low micromolar range were found in four out of five macrocyclic complexes studied, demonstrating their effective ability to scavenge the superoxide anion. The IC50 values obtained with the NBT assay for the macrocyclic copper(II) complexes, were consistently higher, approximately threefold, than those obtained with the DHE assay. Spectroscopic and electrochemical studies were performed in order to correlate the structural features of the complexes with their superoxide scavenger activity. Cytotoxicity assays were also performed using the MTT method in V79 mammalian cells and we found that the complexes, in the range of concentrations tested in the superoxide scavenging assays were not considerably toxic. In summary, some of the presented macrocyclic copper(II) complexes, specially those with a high stability constant and low IC50 appear to be promising superoxide scavenger agents, and should be considered for further biological assays. (c) 2007 Elsevier Inc. All rights reserved.